Regulation of mRNA translation by a photoriboswitch - Rotstan, Kelly A; Abdelsayed, Michael M; Passalacqua, Luiz Fm; Chizzolini, Fabio; Sudarshan, Kasireddy; Chamberlin, A Richard; Míšek, Jiří; Luptak, Andrej (eLife, 2020)
Optogenetic tools have revolutionized the study of receptor-mediated processes, but such tools are lacking for RNA-controlled systems. In particular, light-activated regulatory RNAs are needed for spatiotemporal control of gene expression. To fill this gap, we used in vitro selection to isolate a novel riboswitch that selectively binds the trans isoform of a stiff-stilbene (amino-tSS)-a rapidly and reversibly photoisomerizing small molecule. Structural probing revealed that the RNA binds amino-tSS about 100-times stronger than the cis photoisoform (amino-cSS). In vitro and in vivo functional analysis showed that the riboswitch, termed Werewolf-1 (Were-1), inhibits translation of a downstream open reading frame when bound to amino-tSS. Photoisomerization of the ligand with a sub-millisecond pulse of light induced the protein expression. In contrast, amino-cSS supported protein expression, which was inhibited upon photoisomerization to amino-tSS. Reversible photoregulation of gene expression using a genetically encoded RNA will likely facilitate high-resolution spatiotemporal analysis of complex RNA processes.
Keywords: stilbene; Gene Expression Regulation, Bacterial; proteosyntéza; photoregulation; Escherichia coli; bakteriální RNA; messenger RNA; aptamer; regulace genové exprese u bakterií; RNA, Messenger; riboswitch; spektrální analýza; biochemistry; translation initiation; Riboswitch; RNA, Bacterial; luciferase; chemical biology; Protein Biosynthesis; E. coli; Spectrum Analysis